Underwater Communication Using Wireless Sensor Networks - P. , Renuka Devi; R. , Niverthana; P. , Sampriti (International Journal of Psychosocial Rehabilitation, 2020)
Underwater wireless communications have gained considerable interest during the last years. Underwater communication refers to the technique of sending and receiving messages below water. Underwater communication is extremely attributable to factors like various widespread, little accessible transfer speed and incredible signal weakening, particularly over long ranges. Underwater communication has lower information rates than earthly correspondence. The proposed framework utilizes remote sensor systems associated in a chain way. It wipes out the challenges in go limitations and makes information move increasingly productive. A correspondence plot called AA-RP (AUV-Aided Routing Method Integrated Path Planning) is utilized. In AA-RP, AUV gathers information from sensor hubs in a unique way, which is arranged without anyone else's input simultaneously. At the point when sensor hubs send information to the next bounce, a piece of them sends information parcels straightforwardly, which can decrease the vitality utilization. Depending on the dynamic way of AUVs, the system topology can be modified, and these sensor hubs, which are close to sink hubs, can defeat the vitality opening issue.